Atypical longitudinal development of functional connectivity in adolescents with autism spectrum disorder. Issue 1 (30th October 2018) - Lawrence, Katherine E.; Hernandez, Leanna M.; Bookheimer, Susan Y.; Dapretto, Mirella
Abstract : Autism spectrum disorder (ASD) is consistently associated with alterations in brain connectivity, but there are conflicting results as to where and when individuals with ASD display increased or reduced functional connectivity. Such inconsistent findings may be driven by atypical neurodevelopmental trajectories in ASD during adolescence, but no longitudinal studies to date have investigated this hypothesis. We thus examined the functional connectivity of three neurocognitive resting‐state networks—the default mode network (DMN), salience network, and central executive network (CEN)—in a longitudinal sample of youth with ASD ( n = 16) and without ASD ( n = 22) studied during early/mid‐ and late adolescence. Functional connectivity between the CEN and the DMN displayed significantly altered developmental trajectories in ASD: typically developing (TD) controls—but not youth with ASD—exhibited an increase in negative functional connectivity between these two networks with age. This significant interaction was due to the ASD group displaying less negative functional connectivity than the TD group during late adolescence only, with no significant group differences in early/mid‐adolescence. These preliminary findings suggest a localized age‐dependency of functional connectivity alterations in ASD and underscore the importance of considering age when examining brain connectivity. Autism Research 2019, 12: 53–65 . © 2018 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Brain connectivity may develop differently during adolescence in youth with autism spectrum disorder (ASD). We looked at changes in brain connectivity over time within individuals and found that, for some brain regions, adolescents with ASD did not show the same changes in brain connectivity that typically developing adolescents did. This suggests it is important to consider age when studying brain connectivity in ASD.